2014
DOI: 10.1590/0103-6440201302431
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intracanal Formulation Containing Silver Nanoparticles

Abstract: This study aimed to synthetize, characterize and evaluate the antimicrobial properties of silver nanoparticles to be used in the development of a root intracanal formulation. Silver nanoparticles (AgNPs) were obtained by reduction of silver nitrate with sodium borohydride and characterized by UV-Visible spectrophotometry, scanning electron microscopy (SEM) and dynamic light scattering (DLS). The antimicrobial activity of nanoparticle formulation was evaluated by determinations of the minimum inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…Enterococcus faecalis as the most well-known enterococci species is in charge of almost all persistent periradicular lesions (4,5). Recent studies have reported the excellent antibacterial activity of different synthesized AgNPs against planktonic E. faecalis (29)(30)(31). However, these studies were limited by the lack of investigation on antimicrobial properties of these nanoparticles against the biofilm E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus faecalis as the most well-known enterococci species is in charge of almost all persistent periradicular lesions (4,5). Recent studies have reported the excellent antibacterial activity of different synthesized AgNPs against planktonic E. faecalis (29)(30)(31). However, these studies were limited by the lack of investigation on antimicrobial properties of these nanoparticles against the biofilm E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…The sustained action was absent for both NaOCl and CHX. Bruniera et al developed silver nanoparticles that were transported in to the root canal using a hydroxyethylcellulose polymer gel . The formulation was bactericidal to several species (found within root canal systems) including Escherichia coli, E. faecalis, Pseudomonas aeruginosa, and Streptococcus mutans .…”
Section: Endodontic Materialsmentioning
confidence: 99%
“…Bruniera et al developed silver nanoparticles that were transported in to the root canal using a hydroxyethylcellulose polymer gel. 72 The formulation was bactericidal to several species (found within root canal systems) including Escherichia coli, E. faecalis, Pseudomonas aeruginosa, and Streptococcus mutans. In addition, the authors claimed that the fluidity and homogeneity of the formulation would allow for penetration into the dentinal tubules.…”
Section: Irrigationmentioning
confidence: 99%
“…Chlorhexidine-loaded polymeric nanocapsule with superior antimicrobial activity was developed by interfacial deposition method [45]. Solid lipid nanoparticles of silver showed better antiseptic activity [46].…”
Section: Nanomaterials In Antisepticsmentioning
confidence: 99%